A β-hairpin peptide with pH-controlled affinity for tumor cells. Issue 4 (7th December 2021) - Nishimura, Shin-nosuke; Nishida, Kei; Tanaka, Masaru
Abstract : This peptide undergoes a pH-driven conformational switch between a random coil structure with a flexible linear RGD epitope and a β-hairpin structure with a rigid RGD loop. The β-hairpin-structured peptide is more readily internalized by tumor cells. Abstract : Considering that the pH in the tumor microenvironment is dysregulated, we designed a β-hairpin peptide (SSRFEWEFESS D PRGDPSSRFEWEFESS). The configuration of the peptide switched from a flexible linear to a rigid loop structure under weakly acidic conditions. The peptide internalized by tumor cells increased significantly under weakly acidic conditions.